Courageous World Changers: 50 True Stories of Daring Women of God - Redmond, Shirley-Raye, 1955-; Longhi, Katya (Eugene, Oregon : Harvest Kids, Harvest House Publishers, 2020)
"Meet women who have used their God-given talents to live out their faith to the fullest. They come from a variety of backgrounds, eras, and ethnicities, but each one has answered the Lords call on their life in bold and innovative ways. Children of all ages will be inspired by the stories of Corrie ten Boom--activist, author, and Holocaust survivor ; Laurie Hernandez--gymnast who won both gold and silver medals in her sport ; Florence Nightingale--health care reformer ; Madeline LEngle-- author of childrens literature ; Mother Teresa-- missionary and winner of the Nobel Peace Prize. These and the 45 other female spiritual role models featured in this book have made a profound impact on the world around them, and in many cases changed the course of history. Strong, smart, and sometimes outspoken, these women are tremendous examples of Gods love in action. These inspiring profiles will captivate kids imaginations and encourage them to discover their own gifts and how they can use them to glorify God"--
Keywords: Christian women -- Biography; Juvenile literature; Women in Christianity -- Biography; Juvenile literature; Christian women -- Biography; Women in Christianity -- Biography; Christianity